Transformation Products of Hazardous Cyanobacterial Metabolites in Water - Hiskia, Anastasia; Triantis, Theodoros M.; Antoniou, Maria G.; De La Cruz, Armah A.; O'Shea, Kevin; Song, Weihua; Fotiou, Theodora; Kaloudis, Triantafyllos; He, Xuexiang; Andersen, Joel; Dionysiou, Dionysios D. (My University, 2014)
Cyanobacteria are often grouped into primary and secondary metabolites, wherein the former are essential for growth, development and reproduction of the organism while the latter are indirectly involved in the organisms' survival but their absence does not result in immediate death of the organism. These secondary metabolites are the main focus of this chapter. Cyanobacteria secondary metabolites, whether constitutive or induced, play a key role in their interactions with the environment. Some of these metabolites include taste and odor compounds such as geosmin (GSM) and 2-methylisoborneol (MIB), anti-microbials, terpenoids, lactones, metal chelators, protease inhibitors, indole alkaloids and potent toxins, frequently called cyanobacterial toxins or cyanotoxins (produced by cyanobacteria commonly found in surface water supplies), known to affect a wide range of living organisms. The chapter reviews some of the hazardous secondary metabolites produced by cyanobacteria and their potential transformation products (TPs) formed during various transformation processes.
Keywords: 2-methylisoborneol (MIB); Cyanotoxins; Geosmin (GSM); Hazardous cyanobacterial secondary metabolites; Taste and odor compounds; Taste and odor compounds